Variation in Presentation and Presence of DNA Adducts and p53 Mutations in Patients with Endemic Nephropathy - an Environmental Form of the Aristolochic Acid Nephropathy - Sandra Karanović; Ivana Vuković Lela; Bojan Jelaković; Kathleen G. Dickman; Anamarija Kovač Peić; Damir Dittrich; Matej Knežević; Vesna Matijević; Andrea S. Fernandes; Frederick Miller (Karger Publishers, 2013)
Background: Endemic nephropathy (EN) and associated urothelial cell cancers (UUC) are an environmental form of aristolochic acid nephropathy where the most probable rout of ingestion of aristolochic acid (AA) was made by bread contaminated with AA, leading to chronic dietary intoxication. Clinical courses of three members of the same family, similarly exposed to toxin, who exhibited different clinical courses of the disease are presented. Methods: Questionnaires on AA exposure were taken. Tissue samples were obtained during therapeutic nephrouretectomies. Histopathology, immunohistochemical detection of p53, p53 mutation screening in tumor DNA and analysis on the presence of aristolactam (AL)-DNA adducts were performed. Results: Case 1 had UUC with typical EN histopathological signs, whereas Case 2 had bilateral UUCs with typical EN histopathological signs. In contrast, the patient in Case 3 initially showed renal insufficiency, complicated afterwards by right UUC, and later on by left UUC with histopathological end-stage chronic changes but without typical EN changes. AA-DNA adducts and specific p53 mutational spectra (A:T→ T:A transversion) were found in tissues of cases 1 and 2. Conclusion: Diverse clinical courses seem to be related not to differences in exposure but to differences in metabolic activation or detoxification of AA and/or DNA repair resulting from different genetic polymorphisms.